Sociopoietic Constructivism - Arnold Cathalifaud, Marcelo (MAD, 2010)
This article discusses the concept of "sociopoietic constructivism" as a strategy of scientific knowledge. The presentation is organized in three sections: the first presents the constructivist epistemology as a self-reflexive mechanism of society; in the central part, in the central part, the fundaments that they characterize to its variant assigned to the program, and finally, some of its projections to the research through the second-order observation.